2016
DOI: 10.1039/c6ra00359a
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, morphological and mechanical investigations on ethylene octene copolymer toughened polypropylene prepared by continuous electron induced reactive processing

Abstract: EOC toughened PP with increased interfacial adhesion due to EOC–PP grafting was prepared by continuous EIReP and in continuation the rheological, morphological and mechanical properties of EOC toughened samples were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The controllable properties based on the octene content, besides excellent processability of EOC, have widen its application areas. The results indicated that by applying the suitable compatibilization, EOC could desirably modify the toughness and the impact resistance of a wide range of thermoplastics such as PP, PET, polyamide 6, and PS . To the best of our knowledge, the role of nanoclay platelets as a compatibilizer for PS/EOC blend systems and how they affect the interfacial interactions between phases and their rheological and mechanical properties, besides their morphology, have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The controllable properties based on the octene content, besides excellent processability of EOC, have widen its application areas. The results indicated that by applying the suitable compatibilization, EOC could desirably modify the toughness and the impact resistance of a wide range of thermoplastics such as PP, PET, polyamide 6, and PS . To the best of our knowledge, the role of nanoclay platelets as a compatibilizer for PS/EOC blend systems and how they affect the interfacial interactions between phases and their rheological and mechanical properties, besides their morphology, have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that by applying the suitable compatibilization, EOC could desirably modify the toughness and the impact resistance of a wide range of thermoplastics such as PP, PET, polyamide 6, and PS. [16][17][18][19][20][21][22] To the best of our knowledge, the role of nanoclay platelets as a compatibilizer for PS/EOC blend systems and how they affect the interfacial interactions between phases and their rheological and mechanical properties, besides their morphology, have not been investigated yet. Therefore, in this contribution, the compatibilization role of montmorillonite nanoclay (Cloisite 20A) at different loadings is investigated for immiscible PS/EOC blends.…”
mentioning
confidence: 99%
“…The biodegradable PCL [Capa 6800, M n : 75,000 ± 3000 g mol −1 , dispersity index (DI): 2.4 ± 0.2; T m : 58 °C; crystallinity: 39%] was purchased from the Perstorp Group, Perstorp, Sweden. The PCL is intended to be used as toughening component for polylactide (PLA, 4032D, M n : 69,000 ± 2000 g mol −1 , DI: 2.6 ± 0.3) during electron‐induced reactive processing . In order to fulfill the requirements of melt blending, virgin PCL was masticated by melt mixing in air atmosphere at a temperature of 80 °C for 5 min to modify its viscosity and surface energy.…”
Section: Methodsmentioning
confidence: 99%
“…The PCL is intended to be used as toughening component for polylactide (PLA, 4032D, M n : 69,000 AE 2000 g mol −1 , DI: 2.6 AE 0.3) during electron-induced reactive processing. 20 In order to fulfill the requirements of melt blending, virgin PCL was masticated by melt mixing in air atmosphere at a temperature of 80 C for 5 min to modify its viscosity and surface energy. This masticated PCL [(mPCL), crystallinity: 34%] was used as raw material for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The controllable properties based on the octene content, besides excellent processability of EOC, have widen its application areas. The results indicated that by applying the suitable compatibilization, EOC could desirably modify the toughness and the impact resistance of a wide range of thermoplastics such as polypropylene (PP) at relatively low temperatures, poly(ethylene terephthalate) (PET) and polyamide 6 . However, there are limited works on the PS/EOC blends.…”
Section: Introductionmentioning
confidence: 99%